Meningkatkan Pengetahuan dan Minat Gen-Z untuk Berkarir di Dunia Startup dengan Webinar “Startup for Gen-Z: Is It Possible?” - Slamet Slamet; Purwono Purwono; Sony Kartika Wibisono; Bala Putra Dewa (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
Indonesia is one of the countries with the best startup developments in the world which ranks 6th in the country with the highest number of startups. However, the quality of Indonesian human resources, which are able to meet the qualifications of startup companies, is still low. To that end, the devotees do community service, namely by holding a webinar with the theme "Startup for Gen-Z, Is It Possible?". This webinar aims to motivate, increase knowledge, and provide guidance to webinar participants, especially Generation Z, for a career in the startup world. Gen-Z can be a founder or work in a startup company. In addition, Gen-Z can also take advantage of startups to start small businesses. The stages of implementing this service are analysis, problem determination, solutions offered, outcomes, and evaluation. Participants expressed a high level of satisfaction with the implementation of the webinar “Startup for Gen-Z: Is It Possible?” with an average satisfaction evaluation result of 4,635 Likert scale 1 to 5.